The rise of weekly insulins: addressing the challenges of type 2 diabetes care in Brazil - André Gustavo Daher Vianna; Daniely Freitas Alves; Taís Silveira Assmann; Rosângela Roginski Réa (Diabetology & Metabolic Syndrome)
Abstract Background Type 2 diabetes mellitus (T2D) is a global health concern with a rising prevalence, particularly in Brazil. Insulin therapy plays a crucial role in managing T2D, helping to maintain glucose and energy homeostasis. Moreover, early initiation of insulin is crucial for hyperglycemic control and prevention of chronic complications. Clinical guidelines recommend initiating insulin when other treatments fail. However, several barriers may delay its initiation, contributing to therapeutic inertia and patients’ non-adherence. These barriers include fear of hypoglycemia, lack of adherence, the need for glucose monitoring, the injection method of insulin administration, social rejection associated with the stigma of injections, fear of weight gain, a sense of therapeutic failure at initiation, and lack of experience among some healthcare professionals. Main body of the abstract : In this context, the development of once-weekly insulin formulations could improve initial acceptance, adherence, treatment satisfaction, and consequently, the quality of life for patients. Currently, two once-weekly insulin treatments, insulin icodec and efsitora alfa, have shown promise in clinical trials, demonstrating efficacy and safety profiles similar or better than those of daily insulin therapies. Short conclusion These once-weekly insulins have the potential to emerge as landmark achievements in the evolution of insulin therapy. This narrative review aims to evaluate the role of weekly insulins in managing T2D, providing insights into the potential benefits, challenges, and opportunities associated with a new weekly insulin therapy, specially within the Brazilian context.